RUSSIAN MILITARY PRESENCE IN THE SOUTH CAUCASUS: IMPACT ON THE GEOPOLITICAL SITUATION IN THE REGION AND US INTERESTS (Вісник: Міжнародні відносини, 2024)
Background.  For three decades, the South Caucasus region has been a hotbed of political instability and security tensions due to a series of armed conflicts. The region's geographical location at the intersection of east-west routes makes it important for various actors in international relations. Among them is the Russian Federation, which views the South Caucasus as a strategically important region that it has included in its sphere of influence for decades. At the same time, there are other states that are interested in the South Caucasus, including the United States of America. The concentration of Russian and US interests in this small area leads to increased competition for influence between us in the region and affects regional geopolitical dynamics.Methods. The following methods were used in the study: analytical, historical, comparative, and content analysis.Results. The history of Russia's military presence in the South Caucasus dates back to the imperial period. With various modifications, Russian troops are currently deployed in one way or another in the 3 South Caucasus states. Russia has an impact on both the political situation and the course of armed conflicts in the region, sometimes becoming a significant factor in changing the situation, as was the case with the conflicts in Georgia. The full-scale invasion of Ukraine by the Russian Federation has led to a rethinking by the leadership of the region's states of the expediency of having foreign troops on their territory. Nevertheless, even in such circumstances, Russia is struggling to maintain its military presence in order to maintain its influence in the region. This policy of the Russian Federation, in turn, clashes with the interests of the United States in the South Caucasus, which is interested in weakening Russia's influence and intercepting regional initiatives. The United States seeks to minimise Russia's military presence in the region, thereby depriving Russia of a significant lever of control over the region, and to increase its own involvement in regional processes.Conclusions. Russia has historically had strong influence and strategic interests in the South Caucasus. Its military presence is a key tool for ensuring Russia's influence over the South Caucasus states. However, in recent decades, other actors, including the United States, have also shown interest in the region. The United States has its own strategic interests in the South Caucasus: ensuring peace and stability, promoting democratic values, and combating Russian expansion, which creates a confrontation between Russia and the United States for leadership. The conflict between the two gives rise to various challenges and contradictions, including views on conflict resolution and competition in the economic and energy sectors. Russia will continue its active policy in the region, which challenges US strategic interests. The United States is expected to respond in an effort to protect its interests and reduce Russian influence in the South Caucasus.
Keywords: South Caucasus, the Russian Federation, the United States, military presence, geopolitical interests, sphere of influence, armed conflicts, geopolitical situation